0713 Night-to-night Variability In Objective Sleep Differs By Perception Of Unmet Basic Needs Among Inner-city Women. (27th April 2018) - Lillis, T A; Fischer, A; Aranda, F; Burgess, H J; Gerhart, J; Burns, J; Purim-Shem-Tov, Y; Hobfoll, S E
Abstract: Introduction: Increased sleep variability has been linked with a number of poor health outcomes and low socioeconomic status but has not been examined in relation to perception of unmet basic needs. Night-to-night sleep variability was examined in relation to the perception of unmet basic needs among a diverse sample of inner-city women presenting to the Emergency Department (ED) with an acute pain complaint. Methods: As part of an ongoing, longitudinal study examining the relationship between acute pain and trauma among inner-city women presenting to the ED, 44 female participants (41% Black, 39% Latina/Hispanic, 11%, White, 9% Other; M Age = 28 years) completed a week of continuous wrist actigraphy after their baseline study interview. Participants' perception of unmet basic needs was assessed at baseline and wrist actigraphy assessed objective Total Sleep Time (TST), Wake After Sleep Onset (WASO), and percent of time spent asleep (%sleep). Night-to-night variability in objective sleep parameters was calculated with the root mean squared successive difference (RMSSD). Results: The sample was evenly split between participants who rated their income as enough to meet their basic needs (n=22) and those who rated their income as inadequate to meet their basic needs (n = 22). A series of one-way analyses of variance (ANOVA) revealed that participants who rated their income as inadequate to meet their basic needs had significantly higher RMSSD values for TST (F = 8.67), WASO (F = 9.51), and %sleep (F = 11.97) than participants who rated their income as enough to meet their basic needs (all p 's < .05). These outcomes were not accounted for by differences in race/ethnicity, education, or employment. Conclusion: Consistent with prior research in sleep and health disparities, participants who perceived their income as inadequate to meet their basic needs had greater variability in all objective sleep measures than participants who perceived their income as enough to meet their basic needs. Additional investigation is warranted into the mechanisms underlying greater variability in objectively measured sleep among individuals with unmet needs. Support (If Any): 5R01DA039522-03.